2020
DOI: 10.3390/met11010052
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Deformation Behaviour of Chiral Auxetic Lattices at Low and High Strain-Rates

Abstract: The mechanical behaviour of three different auxetic cellular structures, hexa-chiral 2D, tetra-chiral 2D and tetra-chiral 3D, was experimentally investigated in this study. The structures were produced with the powder bed fusion method (PBF) from an austenitic stainless steel alloy. The fundamental material mechanical properties of the sample structures were determined with classic quasi-static compressive tests, where the deformation process was captured by a high-resolution digital camera. The Split Hopkinso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Auxetic behaviour of lattice structures is typically assessed by the evaluation of Poisson's ratio, which is supposed to gain negative values for auxetic materials [21,22]. However, this property was not evaluated in this study due to the geometry of the investigated specimens.…”
Section: Auxeticitymentioning
confidence: 99%
See 1 more Smart Citation
“…Auxetic behaviour of lattice structures is typically assessed by the evaluation of Poisson's ratio, which is supposed to gain negative values for auxetic materials [21,22]. However, this property was not evaluated in this study due to the geometry of the investigated specimens.…”
Section: Auxeticitymentioning
confidence: 99%
“…Regarding the impact energy absorption capability of auxetic structures, resulting from a stress enhancement occurring under dynamic loading conditions, a significant number of recent studies have focused on investigation into this property [17][18][19]. While some of the authors demonstrated the strain-rate sensitivity of auxetic structures [20][21][22], others indicated rather non-strain-rate-dependent behaviour for specific structures [23]. Thus, further investigation into the possible strain-rate sensitivity of auxetic lattices is still necessary.…”
Section: Introductionmentioning
confidence: 99%
“…In this field, the strain rate-dependency of such porous solids is given by the architecture of the lattice and the base material used for its production. Here, we have already shown that a split Hopkinson pressure bar (SHPB) instrumented with a high-speed camera can be used to assess the dynamic compressive response of various auxetic lattices manufactured by LPBF from 316L powdered austenitic steel [ 15 , 16 , 17 ]. The SHPB apparatus has also been used to evaluate the influence of elevated and reduced temperatures on the deformation response of steel auxetic lattices [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Materials 2022, 15, 4490 2 of 19 structures, metallic auxetic metamaterials exhibit increased yield strength, energy absorption [2], and energy dissipation [3], especially at high rates of strain. The extensive elastoplastic deformation of the internal structure yields a characteristic stress plateau at increasing strains and, therefore, enhanced energy absorption capabilities [4][5][6]. Predominant bending deformation, as seen in chiral structures specifically, provides an even higher energy absorption potential [7,8].…”
Section: Introductionmentioning
confidence: 99%